Certain Properties of Generalized M-Series under Generalized Fractional Integral Operators - D. L. Suthar; Fasil Gidaf; Mitku Andualem (Journal of Mathematics)
The aim of this study is to introduce new (presumed) generalized fractional integral operators involving I-function as a kernel. In addition, two theorems have been developed under these operators that provide an image formula for this generalized M-series and also to study the different properties of the generalized M-series. The corresponding assertions in terms of Euler and Laplace transform methods are presented. Due to the general nature of the I-function and the generalized M-series, a number of results involving special functions can be achieved only by making appropriate values for the parameters.